Teachers’ Perspectives on the Transition from Early Childhood Education to Grade One - Ali Khamis; Mubarok Somantri; Ernawulan Syaodih (Elementary Teacher Education Program, Majalengka University, 2026)
Moving from ECE to Grade One is a pivotal step that can either support or disrupt children's early learning, especially when classroom expectations change abruptly. Yet, evidence from developing education systems remains limited, and little is known about how teachers in Zanzibar interpret and manage this transition. Therefore, this study aims to address that gap by exploring teachers' perspectives on the transition from ECE to Grade One in Zanzibar's unique cultural and linguistic context. This study employed a qualitative descriptive design, involving six teachers: 3 from ECE and 3 from lower primary. Data were collected through interviews and analysed thematically to identify recurring patterns in teachers' experiences. The findings revealed five interconnected themes: First, teachers primarily framed readiness for Grade One in terms of basic literacy skills, chronological age, and children's independence and social competence. Second, early adjustment is often marked by emotional distress and uneven preparedness, particularly for children without preschool experience. Third, teachers described a sharp pedagogical shift, compounded by changes in the language of instruction and classroom routines. Fourth, overcrowded classes, limited learning materials, inadequate infrastructure, and scarce professional support constrained teachers' ability to respond to diverse learning needs. Finally, teachers recommended stronger alignment between pre-primary and primary settings, sustained parent-teacher collaboration, targeted training on transition support, and reduced class sizes. By foregrounding teachers' perspectives from an underrepresented context, this study positions transition as a shared responsibility of children, families, and schools, and offers practical directions for policy and school-level improvement in Zanzibar and similar settings.